2017
DOI: 10.1007/s40588-017-0072-8
|View full text |Cite
|
Sign up to set email alerts
|

The Loss of Binary: Pushing the Herpesvirus Latency Paradigm

Abstract: Purpose of Review Herpesvirus latency has been viewed as a binary state where replication is either on or off. During latency, gene expression is thought to be restricted to non-coding RNAs or very few proteins so that the virus avoids detection by the immune system. However, a number of recent studies across herpesvirus families call into question the existence of a binary switch for latency, and suggest that latency is far more dynamic than originally presumed. These studies are the focus of this review. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 91 publications
0
15
1
Order By: Relevance
“…Although previous studies have linked low levels of viral transcripts to herpesvirus latency (Collins-McMillen and Goodrum, 2017), our RNA-seq analysis demonstrates that viral associated transcripts were not detected from the integrated HHV-6A genome in both iciHHV-6A and 293-HHV-6A cells. A previous study described four HHV-6B latency-associated transcripts (LATs) in latently infected cells (Kondo et al, 2002); however, these LATs were barely detectable in a more sensitive assay and showed maximal expression during the establishment of latency, and just before the onset of reactivation both in vivo and in vitro (Kondo et al, 2003).…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…Although previous studies have linked low levels of viral transcripts to herpesvirus latency (Collins-McMillen and Goodrum, 2017), our RNA-seq analysis demonstrates that viral associated transcripts were not detected from the integrated HHV-6A genome in both iciHHV-6A and 293-HHV-6A cells. A previous study described four HHV-6B latency-associated transcripts (LATs) in latently infected cells (Kondo et al, 2002); however, these LATs were barely detectable in a more sensitive assay and showed maximal expression during the establishment of latency, and just before the onset of reactivation both in vivo and in vitro (Kondo et al, 2003).…”
Section: Discussioncontrasting
confidence: 76%
“…For alphaherpesviruses, HSV latency is associated with the expression of LATs in some latently infected neurons; however, LAT equivalent transcripts are not expressed in varicella zoster virus (VZV) latency (Kinchington et al, 2012), although a recently discovered latency transcript antisense of ORF61 has been reported (Depledge et al, 2018). Varying degrees of evidence on LATs in both natural HCMV infection and experimental latency models have been reported (Cheng et al, 2017; Shnayder et al, 2018), suggesting that herpesvirus latency may be more complex and dynamic than previously assumed (Goodrum, 2016; Collins-McMillen and Goodrum, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Herpesviruses establish life-long persistent infections in humans and animals. In immunocompetent hosts, they remain in a latent sate in the nucleus of infected cells indefinitely and only reactivate sporadically 1,31 . Given the low level of viral replication under these conditions, a gene drive would not be expected to spread in a predominantly latent infection.…”
Section: Discussionmentioning
confidence: 99%
“…ES may have no differences in age predilection, possibly sero-prevalence rate, and clinical manifestations across populations around the world and have occurred throughout every year with no seasonal variations (26, 27). Herpes virus groups become latent in the host after the initial infection as shown in herpes zoster, herpes labialis, and reactivation of cytomegalovirus and Epstein-Barr virus (EBV) in depressed immune state of the host (28). It was reported that EBV infection or herpes virus 6 infection was related to certain clinical manifestations in KD such as otorrhea or BCG inoculation site inflammation (29, 30).…”
Section: Discussionmentioning
confidence: 99%